Chimpanzee vocal communication: what we know from the wild. (August 2022) - Slocombe, Katie E; Lahiff, Nicole J; Wilke, Claudia; Townsend, Simon W
Abstract : Vocal communication plays a vital role in the daily lives of our closest living relatives, chimpanzees. Unpacking the adaptive function of vocalisations, and the cognitive mechanisms underlying their production and comprehension is not only crucial for understanding chimpanzee behaviour, but also for inferring the capacities of our last common ancestors. Here, we review how observational and experimental methods have advanced our understanding of the vocal production and comprehension of wild chimpanzees. We discuss the impact of social and ecological factors on chimpanzee vocal communication, and review the inroads that have been made in elucidating the cognitive processes underpinning call production. We highlight approaches that may offer substantial future advances in knowledge and argue that whilst challenging to collect, data from wild populations is critical to building a comprehensive and accurate understanding of the communicative and cognitive abilities of our closest living relatives, and to tracing the evolutionary roots of human language. Highlights: We review research focussed on vocal production and comprehension in wild chimpanzees We discuss the impact of socio-ecological factors on chimpanzee vocal communication We examine the extent to which wild chimpanzees produce calls intentionally We highlight approaches that may offer substantial future advances in knowledge